2019
DOI: 10.24059/olj.v23i1.1446
|View full text |Cite
|
Sign up to set email alerts
|

Doctoral E-mentoring: Current Practices and Effective Strategies

Abstract: Effective mentoring has been the cornerstone of a successful doctoral experience. Traditional doctoral education uses an apprenticeship model for mentoring to help students learn what is required as an academic professional. However, online environments present unique challenges to creating and maintaining mentor-mentee relationships. Using keywords specific to e-mentoring and online graduate education, literature searches were conducted to isolate relevant research from the last decade. From this literature, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 24 publications
0
24
0
2
Order By: Relevance
“…This resulted in 24 articles from 20 journals worldwide. We then included literature reviews that focused on graduate mentoring at a distance (Byrnes et al, 2019;Columbaro, 2009;Deshpande, 2017;Nasiri & Mafakheri, 2015), leading to a total of 28 articles from 22 journals worldwide (Table 1). These four literature reviews focused solely on online doctoral student mentoring whereas our broader literature review examined both master's and doctoral student mentoring online across disciplines.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…This resulted in 24 articles from 20 journals worldwide. We then included literature reviews that focused on graduate mentoring at a distance (Byrnes et al, 2019;Columbaro, 2009;Deshpande, 2017;Nasiri & Mafakheri, 2015), leading to a total of 28 articles from 22 journals worldwide (Table 1). These four literature reviews focused solely on online doctoral student mentoring whereas our broader literature review examined both master's and doctoral student mentoring online across disciplines.…”
Section: Methodsmentioning
confidence: 99%
“…Frequent communication has been identified as critical to the online mentoring relationship (Broome et al, 2011;de Janasz & Godshalk, 2013;Jacobs et al, 2015;Kumar & Coe, 2017) as it helps to foster immediacy and reduces temporal distance that can create difficulties in the relationship (Duffy et al, 2018;Nasiri & Mafakheri, 2015). The emphasis on communication in the literature, coupled with students' need for timely, clear, and constructive feedback as well as encouragement, indicated that online mentors should have technical, communication, social, and cognitive competencies (Byrnes et al, 2019;Erichsen et al, 2014;Kumar et al, 2013;Schichtel, 2010). Both faculty mentors and student mentees emphasized the need for an awareness of netiquette-communicating politely and with care online-as asynchronous communication opens the potential for miscommunication due to the absence of body language, vocal intonation, and facial expression.…”
Section: Strategies and Best Practices For Mentoring Online Graduate Students Supporting Online Graduate Studentsmentioning
confidence: 99%
See 1 more Smart Citation
“…No que tange à educação, alguns estudos sobre programas de mentoria existentes em cursos de graduação e pós-graduação têm constatado os benefícios que esta relação traz, tanto para o mentor quanto para o mentorado, tais como, satisfação, produtividade, melhora das relações interpessoais, entre outros (Parker-Katz & Bay, 2008;Robnett et al, 2018;Adriaensen, Bijsmans, & Groen, 2019;Byrnes Junior et al, 2019;Lachenaye et al, 2019;& Ong et al, 2019).…”
Section: Startupsunclassified
“…Alguns estudos têm comprovado a eficácia da mentoria acadêmica realizada para o desenvolvimento de competências de pesquisa em alunos de pós-graduação (Robnett et al, 2018;Byrnes Junior et al, 2019), para o desenvolvimento de competências gerais em estudantes participantes da metodologia de aprendizagem baseada em problemas (PBL) (Adriaensen, Bijsmans, & Groen, 2019), para o desenvolvimento de competências técnicas e de pesquisa em estudantes de medicina (Ong et al, 2019) A mentoria eficaz tem sido associada a taxas de sucesso crescentes (Khan & Gogos, 2013;Pinto Zipp, Cahill, & Clark, 2009), aumentando as taxas de retenção (Khan & Gogos, 2013;Mason, 2012), e ajudando a inserir os alunos na comunidade acadêmica (Curtin, Malley, & Stewart, 2016;Gardner, 2008), enquanto a mentoria ineficaz pode ter efeitos opostos (Jones, 2013). O estudo de Lachenaye et al (2019) apresenta a avaliação de um processo de mentoria por pares, realizado no treinamento de novos profissionais, e que trouxe um maior senso de pertencimento entre os participantes, especialmente em temas semelhantes de sua formação, proporcionando uma maior abertura para o compartilhamento de dificuldades e busca de aprendizados.…”
Section: )unclassified